Comparing the diagnostic accuracy of the newly introduced and existing malaria tests in Northwest Ethiopia - Tilahun Bizuayehu Demass; Belay Bezabih Beyene; Getasew Mulat Bantie; Melaku Tadege; Agumas Alemu Alehegn; Abraham Amsalu Berneh; Mihretu Jegnie; Mulat Addis Beshaw; Amare Alemu Melese; Wondwossen Amogne Degu (PLoS ONE, 2025)
Background Malaria is an important public health issue in Ethiopia. Accurate malaria diagnosis plays a vital role in effective treatment. However, there is limited data on the diagnostic accuracy of the newly introduced rapid diagnostic test (LDH-based RDT) and existing diagnostic methods. Objective This study aimed to compare the diagnostic accuracy of the LDH-based RDT and existing diagnostic methods among uncomplicated malaria patients, 2024. Methods The health-facility-based cross-sectional study was conducted in Dembia and North Achefer districts of the Amhara region. A systematic sampling technique was employed to recruit 460 febrile patients. Each patient’s blood sample was investigated for Plasmodium species by RDT, followed by microscopy by different laboratory professionals. The collected blood film slide was sent to the reference laboratory center, Ethiopian Public Health Institute, for confirmatory analysis. The diagnostic accuracy was assessed, and a kappa value > 0.6 was considered as having good agreement between diagnostic techniques. Results The sensitivity and specificity of pLDH-based RDT were 99.6 and 100% compared to reference laboratory results. There was a very good consensus between pLDH-based RDT and blood film (Kappa: 0.97, p-value = 0.0001). There was also a good consensus between blood film at the local laboratory and pLDH-based RDT (Kappa: 0.748, p-value = 0.0001). However, there was the worst disagreement between clinical diagnosis, pLDH-based RDT, and blood film (Kappa range: -0.987 to -0.739). Conclusion This study revealed that pLDH-based RDT and microscopy had higher accuracy as per the WHO recommendation standard. This study implied that clinical diagnosis of malaria must be supported either by RDT or microscopy.